TUJUAN, FUNGSI DAN PRINSIP EVALUASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI PONDOK PESANTREN SURYANI SURAKARTA - A’yuni, Qurrotul; Pangesti, Juni Swan; Suparman, Muh. Fatahillah (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
This research aims to evaluate the implementation of Islamic Education (PAI) learning at Pondok Pesantren Suryani Surakarta, focusing on the objectives, functions, and principles of the evaluation employed. The research adopts a qualitative method, utilizing data collection through observation, interviews, and document analysis involving teachers and students at the pesantren. The evaluation is intended to identify strengths and weaknesses in the implementation of PAI learning and provide recommendations for improvement and development. The evaluation results indicate that the strengths of PAI learning at Pondok Pesantren Suryani Surakarta include the extensive educational backgrounds and experiences of Islamic teachers, their ability to deliver material effectively, and the creation of a conducive learning environment. The use of the halaqah teaching method also allows for active student interaction in understanding Islamic teachings. However, the evaluation also reveals weaknesses, such as limitations in technological resources and the need to accommodate student diversity. Recommendations for improvement include enhancing access to and the use of technology in learning, adopting more inclusive teaching strategies, and developing teacher competencies. Thus, Pondok Pesantren Suryani Surakarta can continue to enhance the quality of Islamic education, meeting the urgency of shaping the character, morals, and religious values of the younger generation, and making a positive contribution to society.